Advances in Interdisciplinary Practice in Industrial Design Proceedings of the AHFE 2018 International Conference on Interdisciplinary Practice in Industrial Design, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Chung, WonJoon; Shin, Cliff Sungsoo (Advances in Intelligent Systems and Computing, 2019)
This book provides readers with a snapshot of cutting-edge methods and procedures in industrial design, with a particular focus on human-centered and user-experience design, service design, sustainable design and applications of virtual & augmented reality. Reporting on both theoretical and practical investigations aimed at improving industrial design through interdisciplinary collaboration, it covers a wide range of topics - from design strategies to product research and planning, exhibit design, as well as new materials and color research. Based on the AHFE 2018 International Conference on Interdisciplinary Practice in Industrial Design, held on July 21-25, 2018, in Orlando, Florida, USA, the book offers a timely guide for industrial designers, production engineers and computer scientists.